EDUKASI E-BISNIS KEPADA UMKM PEMULA KOTA BATAM - Amirullah, Amirullah; Fiani, Ita; Irawati , Ice; Satriani, Satriani (ASOSIASI IDEBAHASA KEPRI, 2026)
Digital transformation has become a critical necessity for micro, small, and medium enterprises (MSMEs) to enhance competitiveness in the modern economic era. However, many beginner MSMEs in Batam City still face challenges in understanding and implementing e-business concepts as well as utilizing digital platforms for product marketing. This community service program aims to improve the digital knowledge and skills of beginner MSME actors through e-business education and practical workshops. The program was implemented in two stages: an online training session on August 16, 2025, followed by an offline workshop on September 1, 2025. A total of 20 participants, consisting of food and contemporary snack business owners, took part in the activities. Pre- and post-test evaluations indicated a significant improvement in participants’ understanding of e-business concepts, the use of marketplaces and social media, and the creation of visual marketing content using Canva. The program successfully fostered positive changes in participants’ attitudes and motivation to adopt digital marketing strategies in their businesses. Thus, this initiative contributes to strengthening the digital foundation of beginner MSMEs, enabling them to better face market competition and achieve business sustainability in the technology-driven economy.